Comparison of volumes of brain areas in patients with bilateral early high-tension and normal-tension glaucoma in 7 Tesla MRI - Sylwester Matwiejczuk; Anna Niedziałek; Katarzyna Toborek; Mateusz Midura; Dominika Wróbel-Dudzińska; Tomasz Żarnowski; Radosław Pietura; Ewa Kosior-Jarecka (PLoS ONE, 2026)
Background Glaucoma is an optic neuropathy characterized by progressive retinal ganglion cells degeneration and associated visual field defects. Although elevated intraocular pressure is a major risk factor, glaucoma can also develop in individuals with statistically normal intraocular pressure, implying alternative mechanisms such as neurotrophins deprivation and primary lateral geniculate nucleus injury. These mechanisms may suggest a neurodegenerative aspect of the disease. Methods In this study, we evaluated 15 patients with bilateral early-stage normal-tension glaucoma, 10 with bilateral early-stage high-tension glaucoma, and 15 age-matched controls. All participants underwent standard ophthalmic examinations, including visual field testing and retinal nerve fiber layer assessment. High-resolution brain imaging was performed on a 7 Tesla MRI scanner. Volumes of the lateral geniculate nucleus and additional brain structures were quantified using ITK-SNAP and FreeSurfer. Results Lateral geniculate nucleus volumes were significantly reduced in both normal-tension glaucoma and high-tension glaucoma groups compared to controls for left side, with no significant difference between normal-tension glaucoma and high-tension glaucoma. Average lateral geniculate nucleus volume was significantly lower in the normal-tension glaucoma group relative to controls, but not in high-tension glaucoma. Pearson correlation showed moderate positive associations between lateral geniculate nucleus volume and average retinal nerve fiber layer thickness when all participants were analyzed together, but no significant correlations were observed within individual groups. No significant differences in total brain volume or cortical structures (e.g., primary and secondary visual cortices) were observed among the three groups. Although certain non-visual regions, such as entorhinal cortex and fusiform gyrus, exhibited subtle alterations suggestive of early neurodegenerative processes, these differences did not reach statistical significance. Nevertheless, these findings may justify further investigation in larger cohorts to explore their potential as early indicators of neurodegeneration in glaucoma. Conclusion These findings indicate that the impact of glaucoma might not be limited to the optic nerve but could also involve alterations in central visual and non-visual pathways. The use of 7 Tesla MRI showed promise in detecting early structural changes, highlighting the importance of further developing advanced imaging techniques. This could help expand the clinical use of ultra-high-field MRI, enhancing diagnosis and understanding of glaucoma.